2005
DOI: 10.1063/1.2131177
|View full text |Cite
|
Sign up to set email alerts
|

Shell structures in self-assembled InAs quantum dots probed by lateral electron tunneling structures

Abstract: We have investigated electron filling in single InAs quantum dots (QDs) using a lateral electron transport structure, i.e., nanolithographically defined metallic leads with nanogaps. Elliptic InAs QDs with a diameter of ∼60∕80nm exhibited clear shell filling up to 12 electrons before the gate leakage became significant. Shell-dependent charging energies and level quantization energies for the s, p, and d states were determined from the addition energy spectra. Furthermore, it was found that the charging energi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
63
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 16 publications
3
63
0
Order By: Relevance
“…The peak positions are suggestive of the addition spectrum of a 2D circular QD with a parabolic confinement potential; each peak is separated by twice the capacitive charging energy, 2E C , with a further splitting between peaks 2 and 3 and between peaks 6 and 7 corresponding to the energy difference between shells, ΔE. This type of shell structure has been previously observed in InAs QDs (8,9,23,24). Fig.…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…The peak positions are suggestive of the addition spectrum of a 2D circular QD with a parabolic confinement potential; each peak is separated by twice the capacitive charging energy, 2E C , with a further splitting between peaks 2 and 3 and between peaks 6 and 7 corresponding to the energy difference between shells, ΔE. This type of shell structure has been previously observed in InAs QDs (8,9,23,24). Fig.…”
mentioning
confidence: 48%
“…It is instrumentally challenging to study self-assembled QDs via conventional transport and charge sensing methods because of the difficulty in attaching electrodes. Although progress is being made (8)(9)(10)(11)(12), these techniques have very small yield and therefore make it difficult to assess variation in QD electronic properties. Compared to typical QDs studied via transport measurements, in particular lithographically defined QDs, self-assembled QDs can be fabricated to have smaller sizes, stronger confinement potentials, and a more scalable fabrication process, all of which make them attractive for practical applications.…”
mentioning
confidence: 99%
“…A local or anisotropic gating has been applied to InAs SAQDs [8][9][10] and NWQDs 11 to modulate in-situ QD-lead tunneling coupling, and angular anisotropy of SOI energy and g-factor. In our previous study 10 of the electrical tuning of g-factor we identified tunability of the g-tensor only in a two-dimensional (2D) plane and assumed that the QD could be approximated as a disk-like 2D harmonic potential as if often done 12,13 . Studies of the anisotropy of the SOI have however shown that a 3D confinement, arising from the QD shape as well as the metal electrodes asymmetrically contacted to the QD, may be more realistic 8 .…”
mentioning
confidence: 99%
“…Electron tunnelling through single self-assembled InAs quantum dots (QDs) coupled to nano-gap metal electrodes has been intensively investigated. To date, a variety of remarkable properties of the InAs QD transistors has already been revealed, such as artificial-atom properties 11,12 , electrically tunable large g-factors 13 and spin-orbit interaction 5,14,15 , and optical pumping of carriers in the terahertz frequency range 6 . However, electrical tuning of the electronic states in the QDs over a wide range has so far been elusive and remains as a great challenge.…”
mentioning
confidence: 99%
“…Therefore, the use of bottom-up nanostructures as an active channel of transistors becomes increasingly important and attracts considerable attention for their prospective applications, especially to quantum information processing [2][3][4][5][6] . One of the promising techniques for electrical access to extremely small bottom-up nanostructures is the use of nano-gap metal electrodes [7][8][9][10][11] . Electron tunnelling through single self-assembled InAs quantum dots (QDs) coupled to nano-gap metal electrodes has been intensively investigated.…”
mentioning
confidence: 99%